APPLICATION OF HUMAN CAPITAL MANAGEMENT TO IMPROVE HR QUALITY AND COMPANY PERFORMANCE THROUGH THEORY - Hadi Supraptika; Miftah Reza Tama Faturohman; Arnesha Febra Syavera; Putri Giovaningrum; Adi Daen Fahmi (PT. Jurnal Center Indonesia Publisher, 2025)
Implementing human resource management (HCM) is one of the main strategies for improving the quality of human resources (HR) and leading to increased business performance. Human capital theory focuses on the development and utilization of human resources as assets of strategic value. Continuous development of education, training and experience will produce a quality workforce capable of providing maximum contribution to the organization. The aim of this research is to analyze the application of HCM in the context of human resource development as a basis for improving organizational performance. This journal uses a theoretical approach from human resources to explore how investments in developing employee skills, knowledge, and abilities can increase a company's productivity, innovation, and competitiveness in the global marketplace.